English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-19 13:48:39 · 7 answers · asked by Bill B 1 in Science & Mathematics Mathematics

7 answers

love it

2007-01-19 13:56:55 · answer #1 · answered by welllaners 5 · 1 2

Binomial Theorum:

(x+y)^n = Σ(n k) (x^k)y^(n-k)

(2x -1)^5 = Σ (5 k) (2x^k) (-1^ (5-k))

= (2x)^5 + 5(2x)^4(-1) + 10(2x)^3(-1)^2 + 10(2x)^2(-1)^3 + 5(2x)(-1)^4 + (-1)^5)
since -1^n = -1 when n is odd
= (2^5)*x^5 - 5(2^4)x^4 + 10(2^3)x^3 - 10(2^2)x^2 + 5(2^1)x - 1
= 32x^5 -80x^4 + 80x^3 - 40x^2 + 20x -1

2007-01-19 14:11:59 · answer #2 · answered by Brian F 4 · 0 0

(a + b) ^ n = a ^ 5 + 5a ^ 4 * b + 10 a ^ 3 * b ^ 2 + 10a ^ 2 * b ^ 3 + 5ab ^ 4 + b ^ 5

then substitute a = 2x, b = -1

2007-01-19 14:06:19 · answer #3 · answered by HT 2 · 0 0

to amplify the formula (a+b)^n, you persist with pascal's triangle built as follows: ........ a million................... for n=0 ....... a million a million................ for n=a million .......a million 2 a million ................for n=2 ......a million 3 3 a million..............for n=3 .....a million 4 6 4 a million............for n=4 ...a million 5 10 10 5 a million......for n=5 .a million 6 15 20 15 6 a million...for n=6 each and each decision in the triangle is the sum of both promptly above it. those numbers many times is the coefficients of the better formula. as for the variables, you start up with the optimal degree (n) for a and the bottom degree (0) for b and progressively advance by one for a and shrink by a million for b; so the first portion of the expression will be a^6b^0 (meaning a^6) and the only ideal one will be a^0b^6 (meaning b^6). as for the signal, if the formula is (a+b)^n, the signal is continually effective (+). for (a-b)^n, you commerce between + and -, starting up with +. so, the only ideal effect will be: (a-b)^6 = a^6 - 6a^5b + 15a^4b^2 - 20a^3b^3 + 15a^2b^4 - 6ab^5 + b^6 for (2x-5)6, replace a with 2x and b with 5. wish that solutions your question!!

2016-11-25 21:27:44 · answer #4 · answered by schifano 4 · 0 0

I get 32x^5 - 80x^4 + 80x^3 - 40x^2 + 10x - 1

2007-01-19 14:04:09 · answer #5 · answered by Richard S 6 · 0 0

(2x - 1)^5 = 2^5x^5 + (-1)5*2^4x^4 + (-1)^2(5*4/2)2^3x^3 + (-1)^3((5*4*3/(1*2*3))2^2x^2 + (-1)^4(5)(2)x + (-1)^5

2007-01-19 16:02:58 · answer #6 · answered by Helmut 7 · 0 0

for binomial theorem there is formula
Tr+1=nCr(x)^(n-r) y^r
if form is (x+y)^n
use it to find ur ans

2007-01-19 15:00:55 · answer #7 · answered by Anonymous · 0 0

fedest.com, questions and answers